Optimization Study of Decolorization Process of Oyster Mushroom's Chitin Thin Film - Mohd Nizam, Najiha Syahida; Wan Nawawi, Wan Mohd Fazli; Rosli, Wan Amalina; Zailin, Ira Shahira (2018)
This study focuses on decolorizing the thin film using sodium hypochlorite (NaClO) to produce highly transparent chitin nanocomposite from chitin nanofiber. Preparation of the thin film from chitin extract of oyster mushroom (Pleurotus ostreatus) demonstrated in this study. Optimization of decolorization of chitin thin film in sodium hypochlorite (NaCIO) was done by one-factor-at-time (OFAT) and statistical approach using Response Surface Methodology (RSM) in Design expert Software. This is to determine the optimal process conditions of decolorization based on three parameters which are concentration of NaCIO, duration and temperature of the process. The optimization was conducted on the basis of response mechanical properties (tensile strength) of chitin thin film. The OFAT method indicated that the optimum condition for decolorization of thin film was at concentration of 6%, duration of 4 hours and temperature of 30οC with the tensile stress value of 52.57 MPa.